Respostas de genótipos de tomate suscetíveis e resistentes a Oidium neolycopersici e Alternaria solani, localização in situ de espécies reativas de oxigênio e atividade de enzimas relacionadas à defesa - Balbi-Peña, Maria Isabel (2010)
To investigate plant defense responses on two Solanum section Lycopersicon genotypes differing in their resistance against Oidium neolycopersici and Alternaria solani, histopathology, generation and accumulation of reactive oxygen species (ROS) and expression of defenserelated enzymes [guaiacol peroxidase (GPOX), catalase (CAT), polyphenol oxidase (PPO), β-1,3-glucanase (GLU) and chitinase (CHI)] were studied after inoculation with those pathogens. To select one resistant and one susceptible genotype, we studied the fungus development on hosts in the case of tomato powdery mildew and we evaluated disease severity using a droplet inoculation method in the case of tomato early blight. CNPH 1287 (Solanum habrochaites syn. Lycopersicon hirsutum) and cv. 'Santa Cruz Kada' (Solanum lycopersicum syn. L. esculentum) were selected like as resistant and susceptible genotypes, respectively, against both pathogens. Two experiments were performed, where CNPH 1287 and Kada plants were inoculated with both pathogens and tissue samples collected for analysis at different time intervals. Oxidative explosion and hypersensitive response (HR) seem to be associated to resistance in CNPH 1287 (S. habrochaites) genotype against O. neolycopersici but not against A. solani. Higher constitutive levels and increased post-inoculation activity of β-1,3-glucanase and chitinase, increased activity of GPOX and PPO (enzymes involved with defense mechanisms) and CAT (enzyme involved with ROS scavenging) that were observed in resistant genotype CNPH 1287 after inoculation with O. neolycopersici were associated with simultaneously ROS accumulation and HR in the tissues. When inoculated with A. solani, CNPH 12987 showed similar changes in enzyme activity except for catalase, where no significant changes were observed. This agrees with the lower level of ROS accumulation during the A. solani pathogenesis. Gene-for-gene resistance with expression of HR and oxidative explosion were observed against the biotrophic pathogen O. neolycopersici. In the case of the necrotrophic pathogen A. solani, HR and ROS accumulation did not appear to play important roles in the resistance against this pathogen.